Vulnerable Bodies and Volunteer Slaves: Slave Parable Violence in the Rest of Matthew - Neufeld, Edmund (2020)
This article works against an assumed disconnect between the slavery of the parables of Jesus in Matthew and the rest of Jesus’s teaching in Matthew. It takes as a given the position of recent research in these matters, that Roman slavery was often brutal against slaves’ bodies and that slave punishment in these parables corresponds to Roman slavery. This article argues mainly that, in this Gospel, everyone suffers violence against their bodies. The unrighteous endure God’s eschatological judgment on their bodies, the righteous endure bodily persecution, and Jesus himself endures bodily persecution, culminating in a slave’s execution. Thus, the harsh treatment of bodies in the parables coheres with Jesus’s other teaching. This article defends two secondary points. First, in a limited but real sense, the disciples and Jesus himself live as volunteer slaves. Second, although Jesus in Matthew does not openly condemn slavery, this Gospel nonetheless implicitly condemns all human attack against another’s body.